Excellent outcomes in older patients with primary CNS lymphoma treated with R-MPV/cytarabine without whole brain radiotherapy or autologous stem cell transplantation therapy. Issue 1 (2nd January 2021) - Tatarczuch, Maciej; Paul, Erin; Gilberston, Michael; Gregory, Gareth P.; Tam, Constantine; Quach, Hang; Bazargan, Ali; Filshie, Robin; Ku, Matthew; Tey, Amanda; Shortt, Jake; Opat, Stephen
Abstract: Primary CNS lymphoma (PCNSL) in immunocompetent patients is a disease of older adults who are often unsuitable for the high dose therapy or experience substantial morbidity from whole brain radiotherapy. As therapeutic studies in older patients are limited, there is a need for real world data to guide patient care. Here we report a series of 38 consecutive immunocompetent patients with PCNSL treated with curative intent using R-MPV/Ara-C with omission of consolidative radiotherapy in older patients. Outcomes for patients aged < 60 years and > 60 years were similar with overall response rates of 100% vs 85%, ( p = .30), 4-year PFS of 81% vs 82% ( p = .92) and 4-year OS of 80% vs 77% ( p = .52) respectively. This study supports the premise that older patients with PCNSL can be effectively treated with sequential and response-adapted methotrexate (MTX) dosing without the need for WBRT or autologous stem cell transplantation (ASCT).